Banker's duty of confidentiality: withering away? - Mohd. Yasin, Norhashimah (2015)
When the customer opens an account with a bank, there exists a relationship between a banker and customer giving rise to a contractual duty for the banker to keep their customer’s information private and fully confidential. This duty of confidentiality includes customer account transactions, and extends to all customer information. This cardinal duty of banking secrecy has been established in England since 1924 pursuant to the leading case of Tournier v National Provincial and Union Bank of England [1924] 1 KB 461, where the learned judge emphasised that the duty of secrecy under common law was contractual in nature and was to be implied from the banker-customer relationship. In Malaysia, the duty of banker’s confidentiality has been adopted into statutory law. It has been governed and guaranteed under both conventional and Islamic banking statutes namely Financial Services Act 2013 (FSA) and Islamic Financial Services Act 2013 (IFSA) respectively. However, in view of new developments on the secrecy rule, this fundamental banker’s duty to uphold customer’s basic right of secrecy is argued to be taken systematically by the establishment of approved government as well as private agencies such as CCRIS, CTOS, FIS and DCHEQS. Objectives/Purpose: This paper is to analyse how far the fundamental duty of banking secrecy and confidentiality is guaranteed and promoted or this duty is not absolute but qualified by certain exceptions that meets its legitimacy in view of impeding money laundering, terrorism, corruption and other unlawful activities. Methods: The paper relies on primary sources of information which includes various legislation/statutes that provide banking secrecy rule. The critical analysis of BAFIA, FSA, Anti-Money Laundering and Terrorism law and other relevant statutes will be examined. Besides, exploration on case law/precedents is also crucial to show the application of this duty as well as exceptions to its general rule. Results/Findings: On critical analysis, it is submitted that banking duty of secrecy is still preserved and guaranteed so as to protect the innocent customers from being mistreated by virtue of unlawful disclosure of customer’s information. However, to protect against the growing threat of global crime such as money laundering, terrorism financing, and unlawful activities, the overall need to protect the customers’ information and confidentiality is justified to be curtailed as without a lawful disclosure of information from the banks, the effective prevention of the crime cannot be materialised.